REVIEW: THE POTENTIAL OF HERBAL PLANTS AS ANTI-ALOPECIA MEDICINES - Arif Rubianto; Garnadi Jafar; Deden Indra Dinata; Jajang Japar Sodik (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Hair loss, or alopecia, is a common dermatological condition that affects up to 2% of the world's population. It is often caused by genetic factors, such as male or female pattern baldness, but can also be attributed to various environmental factors, an imbalanced diet, or chronic illnesses. While hair loss is not life-threatening, it can lead to significant anxiety, depression, and other psychological issues, ultimately affecting one's quality of life. Various treatments for baldness, including synthetic drugs like minoxidil and finasteride, or herbal remedies, have been approved by the Food and Drug Administration. Although synthetic drugs are effective, they may come with potential side effects. Natural remedies have been proposed as a viable option for treating baldness because many chronic disorders can lead to alopecia. Therefore, this review focuses on identifying efficient alternative treatment agents with limited side effects. Specifically, it considers medicinal plants as potential healing agents for treating baldness. To gather relevant information for this study, several databases were searched, including Scopus, PubMed, and Google Scholar. Comprehensive searches were conducted using various search terms, such as "baldness," "alopecia," "natural remedies for baldness," "herbal treatment for baldness," and others, to extract relevant scientific articles. Many medicinal plants and natural compounds have shown potential for reducing baldness, thanks to their anti-inflammatory and antioxidant properties. According to existing literature, extracts of medicinal plants and formulations derived from plants, such as Eclipta alba (L.) Hassk, Arctium lappa L., Centella asiatica L., Morinda citrifolia, Acorus calamus var. angustatus, Alpinia zerumbet, ...